2021
DOI: 10.3389/fbloc.2021.578721
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Approaches to Scaling the Global Commons

Abstract: The re-emergence of commoning over the last decades is not incidental, but rather indicative of a large-scale transition to a more “generative” organization of society that is oriented toward the planet’s global carrying capacity. Digital commons governance frameworks are of particular importance for a new global paradigm of cooperation, one that can scale the organization of communities around common goals and resources to unprecedented levels of size, complexity and granularity. Distributed Ledger Technologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…ture of data implies that technology, mainly discussed in the field of blockchain, may be leveraged to that aim (Fritsch et al, 2021). However, in light of the above, questions about how commons should organise themselves and their relationship with other communities and actors will always be in need of sustainable answers.…”
Section: …And From Inside To Outsidementioning
confidence: 99%
“…ture of data implies that technology, mainly discussed in the field of blockchain, may be leveraged to that aim (Fritsch et al, 2021). However, in light of the above, questions about how commons should organise themselves and their relationship with other communities and actors will always be in need of sustainable answers.…”
Section: …And From Inside To Outsidementioning
confidence: 99%
“…According to a performance evaluation, an Internet of Things healthcare solution based on Holochain technology is more resource-efficient and offers an adequate level of security and privacy, when compared to a solution based on blockchain (9). As these studies showed, Fritsch et al (32) suggests that Holochain has the potential to enable distributed, participant-led governance models that can be more responsive to local needs and values. This can lead to more sustainable and equitable decisionmaking in medical education, as well as more efficient use of resources.…”
Section: Standpoint 2: Use Holochain Instead Of Blockchainmentioning
confidence: 99%
“…The centralized value system inherent in traditional non-technical governance approaches can undermine the inclusion of diverse perspectives, hinder the realization of equitable outcomes across nation boarder and subpar the efficiency in managing complex systems [40]. Conversely, local community oriented governance, while beneficial for value inclusivity, suffers from the tragedy of the commons [41] and difficulties in scaling [42]. Therefore, a transformative governance tooling that tightly unites social, economic, and technological aspects is pivotal in advancing regenerative development to a higher level of effectiveness.…”
Section: Blockchain For Regenerative Governancementioning
confidence: 99%